2014
DOI: 10.1016/j.yebeh.2013.11.023
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods analysis of support for self-management behaviors: Perspectives of people with epilepsy and their support providers

Abstract: Social support is associated with improved self-management for people with chronic conditions, such as epilepsy; however, little is known about the perceived ease or difficulty of receiving and providing support for epilepsy self-management. We examined patterns of epilepsy self-management support from the perspectives of both people with epilepsy and their support persons. Fifty-three people with epilepsy and 48 support persons completed a survey on epilepsy self-management support. Of these individuals, 22 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…[ 36 ] In common with our results, other mixed methods studies of health-behavior interventions have found that most patients want disease specific information and self-management strategies. [ 37 ] Our intervention was based on behavioural theory and was developed via a formal process involving consumers. The presented qualitative data provide a deeper understanding of the mechanisms associated with the observed program effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] In common with our results, other mixed methods studies of health-behavior interventions have found that most patients want disease specific information and self-management strategies. [ 37 ] Our intervention was based on behavioural theory and was developed via a formal process involving consumers. The presented qualitative data provide a deeper understanding of the mechanisms associated with the observed program effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The value of traditional “offline” social support networks for patient self-management has been demonstrated in earlier studies for epilepsy and other chronic conditions. 16 – 19 Psychosocial interventions that improve self-management have previously been demonstrated to improve the health of the chronically ill. 19 – 21 Furthermore, social interactions have also been directly correlated with improved levels of self-efficacy in the epilepsy population. 10 Because this study was powered for detecting changes in the primary outcome measures, we believe that it would be inappropriate to conclude that social interactions on the forum did not affect the improvements.…”
Section: Discussionmentioning
confidence: 99%
“…For this analysis, we developed a model based on participants’ experiences with living with epilepsy and how the experiences of PWE and PSP are intertwined. The methods for this study have been described elsewhere [29, 30] and are summarized below.…”
Section: Methodsmentioning
confidence: 99%